Psychological Distress and Perceived Burden among Parents of Children with Autism Spectrum Disorder: A Cross-Sectional Study - Solaiman, Mahjabeen Aftab; Morshed, ASM; Morshed, Nahid Mahjabin; Mullick, MSI; Harun, HM Mahmud (The Journal of Ad-din Women's Medical College, 2023)
Notice of withdrawal/removal The article “Psychological distress and perceived burden among parents of children with autism spectrum disorder: a cross-sectional study” which appeared in The Journal of Ad-din Women's Medical College; 10 (1), 12-20 (Jan, 2022) has now been removed from journal’s website for similar articles had already been published in an international journal prior to this one. The Journal of Ad-din Women's Medical College 09 August 2022